Assessing "participation" in forest management: workable methods and unworkable assumptions - Colfer, C.J.P.; Wadley, R.L. (1996)
This paper reports the results of a pre-test in West Kalimantan, Indonesia, of four methods designed to assess the level and nature of participation by local people in forest management quickly and easily. Two of the methods - the "Iterative Continuum Method" (ICM) and the participatory card sorting method - were deemed helpful.One method, the communication network analysis, was discarded in its current form.The final method, the researcher guide on the functions of participation, was felt in need of revision. Although the hypothesised firnctions of participation are not wrong, in our opinion, they reflect a way of looking at forest management which, we concluded, needs rethinking.In our discussion of the change needed we make use of Jordan's concept of "authoritative knowledge" and "social" or "cultural capital" (Berkes and Folke 1994; Ostrom 1994).We also suggest substituting "rights and obligations to manage the forest co-operatively " for "participation"in places like Danau Sentarum Wildlife Reserve (DSWR), where sustainable forest management is being assessed. Finally we conclude that, given the dynamism and complexity that characterise natural forests and their inhabitants, co-operation among all stakeholders in an ongoing dialogue is probably the only way that sustainable forest management can in fact occur.We urge researchers to continue the search for simple, inexpensive and reliable tools for assessing the issue we have called "participation in forest management."